PERANCANGAN ALAT DAN SISTEM ABSENSI NON - PNS BERBASIS RFID DI KECAMATAN RANCASARI BANDUNG - Agung Permana; Muhammad Arie Zulfikar; Rini Suwartika (INFOKOM (Informatika & Komputer), 2021)
Currently, there are still many government offices, especially the Rancasari Bandung District office that do not use technology for the presence of Non-PNS employees, resulting in frequent manipulation of attendance data. Presence manually can cause the District to manually recap attendance data in large quantities, and make the process ineffective and efficient. Therefore, this study aims to discuss the Design of RFID Based Non-PNS Attendance Tools and Systems using NodeMCU ESP8266. So this research can make it easier for the Rancasari Bandung District office to make attendance systems for employees more effective and efficient and don’t take much time. This system is integrated with the website so that when employees make attendance, the data is automatically stored directly into the website database.